Developing biographies: the experiences of children, young people and their parents of living with a long‐term condition. Issue 6 (28th November 2013) - Bray, Lucy; Kirk, Sue; Callery, Peter
Abstract This article reports on data from a qualitative interview study that sought to understand the experiences, choices and actions of children and young people undergoing surgery for a long‐term condition and that of their parents. Using the concept of biography the article examines how the biographies of children, young people and their parents can be influenced by surgery and the ongoing management of a long‐term continence condition. This article challenges previous work that characterises the presence of a condition from birth as a continuous and normal part of the illness experiences of these patients. Although this may be the case in some instances, children, young people and their parents can experience diverse and changing experiences associated with ongoing condition management as well as surgery. Biographical continuity, enrichment and disruption are all relevant concepts for such patients living with a long‐term continence condition. These can be influenced by their previous experiences of their condition, their expectations, and dynamics with parents, including changes associated with development and the increasing independence of young people.